2013
DOI: 10.4067/s0718-221x2013005000025
|View full text |Cite
|
Sign up to set email alerts
|

Efecto De Las Caracteristicas De Harina De Madera en Las Propiedades Físico-Mecánicas Y Térmicas De Polipropileno Reciclado

Abstract: RESUMENPolipropileno reciclado (rPP) proveniente de rafia sintética de grandes sacos postconsumo, fueron reforzados con 50 y 60% de harina de madera de Pinus radiata de dos tamaños de partícula (60 y 100 mesh) a través de un proceso de mezclado en fundido, con y sin polipropileno maleado (MAPP), utilizado como agente acoplante. La procesabilidad de rPP y de compositos a base de madera-rPP fue estudiada en términos del torque del proceso de mezcla, al igual que las propiedades físicas, térmicas y mecánicas, y c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 7 publications
2
11
0
12
Order By: Relevance
“…CHF presented a higher cellulose content On the other hand, CHF and CCF fibers addition generate slight improvements (1 and 8%) on the flexural strength (FS) compared to neat r-PP. These results agree with previous studies found in literature [58][59][60]. However, for both r-PP-fiber biocomposites, MAPP addition causes an increase in FS of 16% in comparison with r-PP.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…CHF presented a higher cellulose content On the other hand, CHF and CCF fibers addition generate slight improvements (1 and 8%) on the flexural strength (FS) compared to neat r-PP. These results agree with previous studies found in literature [58][59][60]. However, for both r-PP-fiber biocomposites, MAPP addition causes an increase in FS of 16% in comparison with r-PP.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…As for the effect of the coupling agent, Reddy et al (2010) note that it contributes to increase the interfacial union between the hydrophylic part of the fiber and the hydrophobic part of polypropylene, which reduces the hydrophilic nature of the composite. Lisperguer et al (2013) state that the increase in the interfacial adherence occurring with the presence of MAPP does not determine the absorption. As it may be observed in Figure 5, composite materials with coupling agent have reduced absorption.…”
Section: Absorciónmentioning
confidence: 95%
“…Además, se observa que el agente acoplante tiene un efecto favorable, ya que reduce la absorción de agua, y alcanza un valor de 24 % con la proporción 50/50 con tamaño de malla -40/+60, pero con la proporción 30/70, tamaño de malla -60/+80, fue de 14 %. Idrus et al (2011), Upadhyaya et al (2012), Lisperguer et al (2013) y Bahari y Krause (2016) indican que la absorción de agua es uno de los principales problemas que tienen los materiales compuestos que contienen mayor cantidad de partículas en su composición. Al respecto, Takatani et al (2008) Figure 5 shows the variation of the mean absorption values and their standard deviation with an immersion period of 2 months; likewise, Table 2 shows the variance.…”
Section: Absorciónunclassified
See 2 more Smart Citations